2020
DOI: 10.1093/ibd/izaa017
|View full text |Cite
|
Sign up to set email alerts
|

NOX1 Regulates Collective and Planktonic Cell Migration: Insights From Patients With Pediatric-Onset IBD and NOX1 Deficiency

Abstract: Background Genetic defects of pediatric-onset inflammatory bowel disease (IBD) provide critical insights into molecular factors controlling intestinal homeostasis. NOX1 has been recently recognized as a major source of reactive oxygen species (ROS) in human colonic epithelial cells. Here we assessed the functional consequences of human NOX1 deficiency with respect to wound healing and epithelial migration by studying pediatric IBD patients presenting with a stop-gain mutation in NOX1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…This result is consistent with a study performed in our lab, where we provide evidence that loss of NoxO1 in mice results in less differentiation of enterocytes and spurs DSS/AOM induced colitis and cancer formation [8]. In contrast, inflammatory bowl disease is associated with TNFα/NFκB induced expression of NoxO1 and increased Nox1 derived ROS formation [9,10]. In stomach, NoxO1 potentially has pro-tumorigenic functions.…”
Section: Introductionsupporting
confidence: 92%
“…This result is consistent with a study performed in our lab, where we provide evidence that loss of NoxO1 in mice results in less differentiation of enterocytes and spurs DSS/AOM induced colitis and cancer formation [8]. In contrast, inflammatory bowl disease is associated with TNFα/NFκB induced expression of NoxO1 and increased Nox1 derived ROS formation [9,10]. In stomach, NoxO1 potentially has pro-tumorigenic functions.…”
Section: Introductionsupporting
confidence: 92%
“…During inflammation of the lung caused by the influenza A virus, NOX1 suppresses inflammation and oxidative stress, and on the contrary, the NOX2 isoform seems to have a pro-inflammatory role in the regulation of influenza A infections ( Selemidis et al, 2013 ). In IBD, it was recently demonstrated that a lowered ROS-production in cells due to the loss of NOX1 is associated with delayed wound healing, cytoskeletal changes, and altered collective cell migration, which affect tissue repair and barrier function ( Khoshnevisan et al, 2020 ). Human bronchial epithelial (NHBE) cells express HYAL2 (hyaluronidase 2), a hyaluronan-degrading enzyme, and ROS increases HYAL2 activity and expression.…”
Section: Discussionmentioning
confidence: 99%
“…ROS produced by epithelial NOX1 contribute to the proliferation and differentiation of colonic epithelial cells by modulating the PI3K/AKT/Wnt and Notch1 signaling pathways (Coant et al, 2010). Furthermore, NOX1-mediated cellular ROS production is required for collective migration of epithelial cells, because defective directional migration and altered cell-cell contact were observed in cells with loss of NOX1 function (Khoshnevisan et al, 2020). Intestinal epithelial cells cover the outermost surface of the mucosa and interface with the lamina propria to form the intestinal mucosal barrier (Quiros and Nusrat, 2019).…”
Section: Discussionmentioning
confidence: 99%